Clinical studies and antimicrobial activity of ciprofloxacin hydrochloride medicated dental gels for periodontal infection - Rao, N G Raghavendra; Rao, K Purushotham; Muthalik, S; Shivanand, A (Asian Journal of Pharmaceutics (AJP), 2014)
For the effective treatment of periodontitis, ciprofloxacin hydrochloride (HCl) medicated dental gels are prepared with different hydrophilic polymers (MC, HPMC, HPC, and HEC) in different concentrations of propylene glycol. The formulations are subjected to various physicochemical studies like pH, spreadability, extrudability, viscosity, drug content, in vitro drug release, and rheological and stability studies. During the rheological studies plots of shear rate versus viscosity showed that all the gels were non-Newtonian and exhibited pseudoplastic behavior. in vitro drug release studies were carried out in the diffusion cell using a pH 7.2 phosphate buffer as a receptor medium. Formulations exhibited an extended release of the drug for over a period of 6 hours and the release depended on the type of polymer and concentrations of propylene glycol used. Stability studies showed no significant variations (P > 0.05) in pH, spreadability, viscosity, extrudability, and drug content. An in vitro release study concluded that hydrocolloid based ciprofloxacin hydrochloride medicated dental gels appear to be probably extend the release of ciprofloxacin hydrochloride. Optimal formulations were selected for in vivo or clinical studies. The clinical evaluation of ciprofloxacin hydrochloride gels was carried out to determine the efficacy in the treatment of periodontitis. Six groups, each containing five patients, were used in the study. All the patients were evaluated for plaque index (PI) and gingival index (GI), probing depth (PD), and bleeding on probing (BOP). In all these studies, two groups were treated with formulations alone and another two groups were treated with formulations along with scaling and root planning. One group was treated with scaling and root planning only, whereas, the last group was treated as control (No treatment). All the groups showed a similar baseline PI. However, the PI values decreased remarkably in the groups treated with formulation along with scaling and root planning when compared to the other groups. Similarly, the results of GI, BOP, and PD also showed a significant reduction (P < 0.05) in the groups treated with formulation along with scaling and root planning compared to other groups. The above studies revealed that the adjunctive use of ciprofloxacin hydrochloride gels along with scaling and root planning results in significant benefits, in the treatment of periodontitis.